Thermal annealing behaviour and gel to crystal transition of a low molecular weight hydrogelator - Barker, Emily; Martin, A.; Garvey, C.; Goh, Ching; Jones, Franca; Mocerino, Mauro; Skelton, B.; Ogden, Mark; Becker, Thomas (RSC Publishing, 2017)
The thermal annealing behaviour of an electrolyte-triggered calixarene hydrogelator is found to depend strongly on the specific metal chloride used. While the lithium chloride gel showed typical gel-sol transitions as a function of temperature, the magnesium chloride gel was found to repeatedly strengthen with heat-cool cycles. Structural investigations using small-angle neutron scattering, and scanning probe microscopy, suggest that the annealing behaviour is associated with a change in morphology of the fibrous structures supporting the gel. On prolonged standing at room temperature, the magnesium chloride gel underwent a gel-crystal transition, with the collapsing gel accompanied by the deposition of crystals of a magnesium complex of the proline-functionalised calix[4]arene gelator.